The Development of "Ummi" Method using Hand Movements to Memorize An-Naba at RQ Muhammad Darwis Colomadu - Fathurohman, Wahid; Nurrohim, Ahmad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Based on the researcher's observations and experiences throughout the learning process at RQ Muhammad Darwis, this study was conducted. The teacher only used face-to-face instruction with ummi method, to help students memorize information. Because of this, learning becomes less conducive to memorization and students become easily bored. Based on these facts, the purpose of this research was to combine the Ummi method with hand movements in RQ Muhammad Darwis Colomadu in order to increase the effectiveness of memorizing, particularly for An - Naba. The first step in this research was to analyze the issues students were having with learning memorization the Koran. The ADDIE approach (Analyze, Design, Develop, Implement, and Evaluate) was applied in this study. Five students who participated in the implementation or trial procedure served as the research subjects. By watching the participating students, research data was gathered. The result study showed a percentage of 75.7%, indicating the validity, interest, and efficacy of the ummi method with hand movement criteria. Thus, it can be concluded that RQ Muhammad Darwis Colomadu may effectively teach memorizing by the use of ummi technique with hand gestures.